THE DEVELOPMENT OF PROJECT-BASED LEARNING TOOLS IN GEOMETRIC MATERIAL - Baharuddin Abbas; Ayu Rahyuni Ali; Sri Sulasteri; Ahmad Farham Majid; Yuspiani Yuspiani (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
The research discusses about project-based on learning tools development in geometric material at class IX MtsN Gowa. This research aims to know the process of the project-based learning tools development which fulfills valid, practical, and effective criteria. The research is Research and Development (R&D) which uses the development model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The development procedure contains 5 steps are: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subject of the research is the students at class IX MTsN Gowa which is in one class, the instruments of the research are the validation sheet, the learning outcome test, student and teacher response questionnaire, observation sheet of the learning process, observation sheet of student activity, and observation sheet of learning management. Based on the result of trials obtained that: (1) RPP 3.24 result of validation learning instrument, 3.41 textbooks, and LKPD 3.26 in each value which obtained in the valid category. (2) Practical based on observation result of learning tools practice with an average of 1.97 is in a fully implemented category, teacher response to textbooks and LKPD gave 100% positive response, the student gave 88.2% positive responses to the textbooks and while LKPD got 82.3% positive responses. (3) Effective based on the result of observation management learning got an average of 3.80 with a very good category, student activity in the very good category with an average of 80.56%, the learning outcome test got an average of 83.82 from 100 maximum scores. In conclusion that learning tools that have been tested fill-up the criteria of valid, practical, and effective.